Spalling of high strength concrete under contact explosive charge - Duc Ngo The; Thang Dam Trong; Thuy Ngo Ngoc (Journal of Applied Science and Engineering)
Spalling is the phenomenon of concrete destruction under the impact of high-speed loads such as impact or explosion at the surface opposite to the load source. Spalling not only causes structural damage but also threats to humans and damages internal equipment by ejecting debris from the surface. Spalling in structures is induced by tensile waves, formed as incident waves propagate and are reflected the free surface (called reflected stress waves). In this study, experimental and simulation methods are applied to analyze the propagation and reflection process of stress waves,as well as the formation of spalling caused by reflected waves. These methods are also used to determine the spalling coefficient of high-strength concrete under contact charge. By changing the mass of the explosive charges and varying sizes of concrete slabs, the amount of explosives needed to induce spalling on each slab is determined. The spalling-resistant thickness is proportional to the relative mass of explosives. The results obtained are considered as a basis for determining the spalling-resistant thickness of protective structures faster and safer.